Priority health problems as a vehicle for undergraduate: problem based learning in community medicine - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
Keywords: health problem, diseases, nutrition, hypertention, stomach pain